The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1203/00006450-199606000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Expression in Cord Blood of Patients with Clinical Chorioamnionitis

Abstract: The objective of this study was to define whether IL-6 is an early marker of infection in the newborn. To correlate the occurrence of clinical chorioamnionitis with the levels of IL-6 expression in neonates, IL-6 was measured in cord plasma by ELISA and in mononuclear cells by reverse transcriptase-PCR before and after mitogenic stimulation. Eight neonates were included in each of the following four groups: elective cesarean section, uncomplicated normal spontaneous vaginal delivery, delivery after prolonged r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…In the absence of neonatal disease, we found that chorioamnionitis was less marked, but still associated with elevated levels of mainly pro-inflammatory cytokines (IL-1b, IL-6, IL-8 and IL-1RA). Singh et al 23 have also reported that clinical chorioamnionitis was associated with elevated IL-6 levels in umbilical serum, even in the absence of neonatal disease. These investigators found that cord blood cells were an unlikely source of IL-6, when the neonates were clinically unaffected 23 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the absence of neonatal disease, we found that chorioamnionitis was less marked, but still associated with elevated levels of mainly pro-inflammatory cytokines (IL-1b, IL-6, IL-8 and IL-1RA). Singh et al 23 have also reported that clinical chorioamnionitis was associated with elevated IL-6 levels in umbilical serum, even in the absence of neonatal disease. These investigators found that cord blood cells were an unlikely source of IL-6, when the neonates were clinically unaffected 23 .…”
Section: Discussionmentioning
confidence: 98%
“…These investigators found that cord blood cells were an unlikely source of IL-6, when the neonates were clinically unaffected 23 . Although it is unclear whether cytokines may cross from placenta during inflammation, our findings, and the findings reported by Singh et al 23 suggest that inflamed placenta tissues could also be a source of cytokines in the fetal circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, early-onset sepsis results from an ascending infection of bacteria from the maternal rectovaginal flora invading the amnion fluid and coming into contact primarily with mucosal cells of the fetal gastrointestinal and respiratory tract. During the last years, several clinical studies, including our own, have demonstrated that levels of proinflammatory cytokines, such as TNF-␣, IL-1␤, IL-6, and IL-8, in plasma are highly elevated in cord blood of neonates with early-onset sepsis (3,4,18,19,27). In the present study, which advantageously could be based upon data on the expression of a variety of cytokines, we were able to show that levels of LBP and sCD14 in plasma also are increased during neonatal early-onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…7.10), very low Apgar scores and the need for resuscitation with ventilation for 1 3 min [18,21]. In order to define a newborn as having perinatal infection, maternal risk factors were taken into consideration, such as prolonged rupture of membranes or chorioamnionitis [22,23]. In addition, infected newborns were diagnosed as having either proven septicaemia (with positive blood cultures) or suspected septicaemia (with at least 3 clinical and 3 laboratory relevant findings).…”
Section: Patientsmentioning
confidence: 99%